A Battle Cry for Our Moment: Revisiting the Two Analyses of Mr. Z. Issue 1 (2nd January 2021) - Kaufmann, Jenny Kahn; Kaufmann, Peter
ABSTRACT: This paper is a battle cry for our current moment. In it, we will return to The Two Analyses of Mr. Z and discuss it as a chronicle of self-emergence that implies Kohut's simultaneous rebellion against his mother's paranoid control and against the pathologizing bent toward narcissism in the Freudian classical tradition. We also will show how the clinical process that Kohut depicts in the case exemplifies a model of emerging from the shadows of traumatizing narcissism that can be more generally applied. Then, we will discuss the case of Susan in terms of how she and Peter joined together to fight back against the traumatizing effect of Trump and her parents. We think that this emergence process parallels what Kohut describes happening in the second analysis of Mr. Z. and illustrates this model of emerging from the shadows of traumatizing narcissism. We end the paper by exhorting all of us to be inspired by Kohut and Susan as examples, to fight back against the forces of a fascism, driven by pathological narcissism, that have arisen all around us. We posit the concept of differentiating rage and appeal to all of us to dig down, find this affect state and express it to take back the power!